BRAF L485–P490 deletion mutant metastatic melanoma sensitive to BRAF and MEK inhibition: A case report and literature review - Zhang, Simeng; Yang, Zichang; Cheng, Yu; Guo, Xiaoyu; Liu, Chang; Wang, Shuo; Zhang, Lingyun (Frontiers in Pharmacology, 2023)
Background: The combination therapy of BARF inhibitors (BRAFis) and MEK inhibitors (MEKis) has been approved as a first-line treatment for metastatic melanoma with BRAF V600 mutants. Recently, BRAF mutations have been divided into three subtypes based on biochemical and signaling characteristics. Unlike V600 mutants that show Class I BRAF mutations, the evidence of using BRAFis and MEKis in patients with Non-V600 BRAF mutations remains unclear. Thus, the exploration of an effective therapy for Non-V600 BRAF mutations in melanoma has attracted much interest. Case presentation: We reported a case of a 64-year-old female metastatic melanoma patient with a novel BRAF p.L485_P490 deletion mutation. The patient received anti-PD1 agent pembrolizumab (100 mg) therapy as the first-line treatment for two cycles which was terminated due to intolerable adverse effect. Considering the p.L485_P490 deletion mutation signal as an active dimer which is akin to Class II BRAF mutation, the patient underwent the dabrafenib and trametinib combination therapy as second-line treatment. After two cycles of combination treatment, the patient achieved a partial response confirmed by radiological examinations. To date, the patient remains progression-free and treatment was well tolerated. Conclusion: The combination therapy of dabrafenib and trametinib has been proven to be an effective method as a later-line therapy for metastatic melanoma patients with Class II BRAF in-frame deletion mutations.